Influencia de los factores estilo de vida, autocontrol de gasto y referencia de grupo en la decisión de compra de teléfonos celulares en la generación z mayores de edad de la zona 6 y 7 de Lima Metropotitana del NSE AB - Hidalgo Falla, Marcelo Eduardo (2023)
The present study will seek to know the preferences of a sector of the population, called generation Z of legal age, focused on zones 6 and 7 of Metropolitan Lima of the NSE AB. For this, it is important to delimit generation Z as all those born after 1995. Likewise, the majority are those who have just entered the labor market or were already there and represent a very important market segment for companies in sale of telecommunications equipment. Consequently, in population terms they are the second most important group after Millennials, those born between 1980 and 1994. (Cerezo, 2016) First of all, the present investigation is oriented in the area of Marketing and consumer behavior of type 34.a1 (Research and market analysis) by the University of Lima. This work will validate the influence of lifestyle factors, self-control of spending and group reference in the decision to purchase cell phones in generation Z of legal age. In relation to this, the selection of a representative sample of the previously mentioned population will be carried out, which according to the Krejcie & Morgan formula, resulted in a total of 380 valid surveys. In the same way, for the methodology, surveys will be used of people from the objective districts that belong to the determined population group. Finally, the responses were loaded into the SPSS statistical program to carry out the normality and Spearman tests, where it resulted that they are non-parametric variables and that the three independent variables had a positive influence on the purchase decision, being the style of life the most important.